2020
DOI: 10.1097/01.asw.0000653160.13611.5d
|View full text |Cite
|
Sign up to set email alerts
|

A Multicenter, Comparative Study of Two Pressure-Redistribution Mattresses with Repositioning Intervals for Critical Care Patients

Abstract: Support surfaces remain an integral component of pressure injury prevention and treatment. Recent research and new technologies coupled with new standards testing created a need for revision of past terms and definitions related to support surfaces. These terms and definitions have been developed to provide a common understanding of terms that refer to basic physical concepts, design considerations, and product characteristics. Thus, the purpose of this document is to provide a glossary of terms and definition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
54
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(59 citation statements)
references
References 23 publications
0
54
0
5
Order By: Relevance
“…Evidence regarding median time to pressure injury development varies; for example, recent acute care evidence shows a 2-5 day median time to pressure injury development when using high density foam mattresses and 4-hour repositioning. 22 TEAM-UP's 28-day follow-up period was longer than prior nursing home randomized control trials' intervention periods. 13,14 Prior research supports the adequacy of the 4-week Intervention time period to permit development of pressure injuries in the sample studied.…”
Section: Limitationsmentioning
confidence: 98%
“…Evidence regarding median time to pressure injury development varies; for example, recent acute care evidence shows a 2-5 day median time to pressure injury development when using high density foam mattresses and 4-hour repositioning. 22 TEAM-UP's 28-day follow-up period was longer than prior nursing home randomized control trials' intervention periods. 13,14 Prior research supports the adequacy of the 4-week Intervention time period to permit development of pressure injuries in the sample studied.…”
Section: Limitationsmentioning
confidence: 98%
“…There was no significant difference in the incidence of PI between APMs and HSFMs (Nixon et al, 2019) and contradicting results were reported in studies comparing APMs and VFMs (Jiang et al, 2020;Sauvage et al, 2017). One study (Sauvage et al, 2017) used an ITT analysis, but the dropout rates for APMs and VFMs were 28% and 17%, respectively.…”
Section: Discussionmentioning
confidence: 91%
“…The use of a viscoelastic foam mattress with patient repositioning every 4 h had similar injury incidence compared with an air mattress with repositioning every 2 h [ 55 ].…”
Section: Resultsmentioning
confidence: 99%